2020
DOI: 10.1002/ps.5725
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of resistance to HPPD‐inhibiting herbicides in a wild radish population via enhanced herbicide metabolism

Abstract: BACKGROUND Relatively new herbicides that target 4‐hydroxyphenylpyruvate dioxygenase (HPPD) are now available for use on the world's great grain crops (rice, wheat, corn and soybean) and for other uses. With widespread and persistent use of HPPD‐inhibiting herbicides, the evolution of HPPD‐inhibiting herbicide resistant weeds is inevitable. Currently, resistance to HPPD‐inhibiting herbicides is known in two weed species, waterhemp and Palmer amaranth. Here, we report a HPPD‐inhibiting herbicide resistant wild … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(66 citation statements)
references
References 38 publications
0
66
0
Order By: Relevance
“…in R . raphanistrum 35 . Hence, metabolic resistance needs to be managed effectively by diverse chemical and non‐chemical methods such as herbicide mixture/rotation and harvest weed seed control, to preserve the valuable TT herbicide technology.…”
Section: Discussionmentioning
confidence: 99%
“…in R . raphanistrum 35 . Hence, metabolic resistance needs to be managed effectively by diverse chemical and non‐chemical methods such as herbicide mixture/rotation and harvest weed seed control, to preserve the valuable TT herbicide technology.…”
Section: Discussionmentioning
confidence: 99%
“…A survey of ALSresistant A. palmeri in Georgia found that more than half of the populations had no ALS target site mutations and exhibited enhanced ALS herbicide metabolism (123). Resistance to HPPD inhibitors has been reported in A. tuberculatus (124,125), A. palmeri (110,126) and recently in R. raphanistrum (127). The resistant biotypes metabolized HPPD inhibitors at a faster rate than the susceptible populations through hydroxylation reactions, indicating a P450 role in the resistance mechanism in the broadleaf species (110,127,128).…”
Section: Cytochrome P450-mediated Herbicide Metabolismmentioning
confidence: 99%
“…Resistance to HPPD inhibitors has been reported in A. tuberculatus (124,125), A. palmeri (110,126) and recently in R. raphanistrum (127). The resistant biotypes metabolized HPPD inhibitors at a faster rate than the susceptible populations through hydroxylation reactions, indicating a P450 role in the resistance mechanism in the broadleaf species (110,127,128). Recently, A. tuberculatus biotypes from Nebraska with resistance to tembotrione and 2,4-D, as well as A. palmeri from Arkansas with resistance to fomesafen, were controlled when a P450 inhibitor was applied (111,113,129).…”
Section: Cytochrome P450-mediated Herbicide Metabolismmentioning
confidence: 99%
“…Resistance to HPPD inhibitors is rare in weeds, having been reported in only two other weed species after having been first reported in A. tuberculatus. 28,67 The first cases of HPPD-inhibitor www.soci.org PJ Tranel wileyonlinelibrary.com/journal/ps resistance in A. tuberculatus were observed in commercial maize seed fields. 16,27 Such production systems rely on HPPD-inhibiting herbicides (because of their crop safety across inbred lines), often are not rotated to other crops, and have high weed pressure due to poor crop competitiveness and dispersed plantinga 'perfect storm' for resistance evolution.…”
Section: Hppd Inhibitorsmentioning
confidence: 99%